New Comprehensive Clinical Classification of the Dry Eye Syndrome Severity 2024. Part 2. Treatment Algorithm — the Opinion of Ophthalmologists - А. V. Trubilin; V. N. Trubilin; E. G. Poluninа; E. A. Kasparova; D. V. Andzhelova; K. A. Mirzabekova; Yu. V. Evstigneeva; K. V. Chinenova; I. A. Leshenko (Oftalʹmologiâ, 2025)
The first part of the article presented the developed clinical classification of the severity of dry eye syndrome 2024, which takes into account not only objective indicators of the state of tear production and the degree of inflammation of the tissues of the ocular surface, but also subjective indicators — patient complaints (SPEED quality of life scale). This classification allows to determine the severity of dry eye syndrome (DES), which in turn makes it possible to choose an adequate volume and type of therapy for this disease. The study presented in this article, conducted on the basis of a questionnaire of ophthalmologist experts (Delphi method), made it possible to formulate an algorithm for treating dry eye syndrome using the developed comprehensive clinical classification of the severity of this pathology. The ophthalmologist expert determined the indications for prescribing various groups of drugs — tear substitutes, corneoprotectors: gels containing dexpanthenol, ointment forms. Anti-inflammatory therapy — dexamethasone, antiallergic, nonsteroidal anti-inflammatory drugs, blood products (autologous/alogeneic serum, PRP), cyclosporine, antiseptics. Physiotherapeutic treatment — eyelid hygiene: warm compresses/irrigation of the eyelid surface with warm water + eyelid self-massage, IPL therapy, Aktiva system, Plasma jett system. The algorithm allows to determine indications for 13 types of dry eye syndrome therapy recommended for use by the international working group The Tear Film & Ocular Surface depending on the severity of dry eye syndrome (mild, moderate, severe), the presence of concomitant pathology or taking medications on an ongoing basis, as well as the duration of dry eye syndrome. Given the high level of expert agreement in the assessment (Randolph kappa coefficient above 0.6) when compiling the algorithm, it can be recommended for use in a wide ophthalmological practice, including primary outpatient care.